تصور مقترح لتوظيف استراتيجية إثارة التساؤلات في تدريس الفقه الإسلامي: Program Model to Employing a Problem-Solving Strategy in Teaching Islamic Jurisprudence - Hammad, Hamza Abed Alkarim (Journal of Islamic Educational Research, 2020)
Many previous studies indicate the prevalence of traditional teaching on Islamic jurisprudence courses, these are the methods that memorize the basis for them, so this paper attempts to suggest the employment of teaching strategy to solve problems as a modern applied model in teaching jurisprudence courses, and followed the descriptive approach by explaining what a strategy is problem solving and its advantages, and the way to conduct lectures according to this strategy, The study concluded with the necessity of developing methods of teaching Islamic jurisprudence. It presented a set of contemporary problems that could be used in the teaching of the personal status course â€œThe Fiqh of Marriage and Divorceâ€.